Differential innate immune response of European seabass (Dicentrarchus labrax) against Streptococcus iniae. Issue 2 (October 2015) - El Aamri, F.; Real, F.; Acosta, F.; Bravo, J.; Román, L.; Déniz, S.; Padilla, D.
Abstract Streptococcus iniae is a Gram-positive bacteria that causes invasive infections with severe septicemia and meningitis, producing high economic losses in marine and continental aquaculture. Head kidney leukocytes of European sea bass (Dicentrarchus labrax) were used to measure the differential innate immune response upon infection with S. iniae. The complete inhibition in the production of intracellular superoxide radicals and total peroxidase content was observed in infected cells. This study also elucidates changes in the relative expression of some immune-related genes. Interleukin 1β, tumor necrosis factor-α and interleukin-6 reached a peak of expression at 4–8 h post-infection, subsequently decreasing significantly up to 48 h post-infection. However, interleukin-10 and Mx protein increased over time, reaching the pick of expression at 48 h post-infection, whereas caspase-3 showed down regulation until 48 h post-infection. The in vivo study of immune related genes show the same kinetics of mRNAs expression as in vitro experience. The proinflammatory cytokines mRNA transcription levels peaked at an earlier time in vivo than in vitro system. Our findings indicate that there is a direct relationship between the dissemination of bacteria and the resulting infection-associated inhibition of respiratory burst, apoptosis, and the pro- and anti-inflammatory gene expression profiles.